The Role of Descending Inhibitory Pathways on Chronic Pain Modulation and Clinical Implications. Issue 7 (20th November 2013) - Kwon, Mikwang; Altin, Murat; Duenas, Hector; Alev, Levent
Abstract The treatment and management of chronic pain is a major challenge for clinicians. Chronic pain is often underdiagnosed and undertreated, and there is a lack of awareness of the pathophysiologic mechanisms that contribute to chronic pain. Chronic pain involves peripheral and central sensitization, as well as the alteration of the pain modulatory pathways. Imbalance between the descending facilitatory systems and the descending inhibitory systems is believed to be involved in chronic pain in pathological conditions. A pharmacological treatment that could restore the balance between these 2 pathways by diminishing the descending facilitatory pain pathways and enhancing the descending inhibitory pain pathways would be a valuable therapeutic option for patients with chronic pain. Due to the lack of evidence for pharmacological options that act on descending facilitation pathways, in this review we summarize the role of the descending inhibitory pain pathways in pain perception. This review will focus primarily on monoaminergic descending inhibitory pain pathways and their contribution to the mechanism of chronic pain and several pharmacological treatment options that enhance these pathways to reduce chronic pain. We describe anatomical structures and neurotransmitters of the descending inhibitory pain pathways that are activated in response to nociceptive pain and altered in response to sustained and persistent pain which leads to chronic pain in various pathological conditions.